Sorption behavior of methylene blue and rhodamine B mixed dyes onto chitosan graft poly (acrylic acid‐co‐2‐acrylamide‐2‐methyl propane sulfonic acid) hydrogel. Issue 7 (2nd January 2018) - Tang, Yaoji; He, Tengteng; Liu, Yangwenyi; Zhou, Bin; Yang, Rui; Zhu, Linhui
Abstract: Chitosan graft poly(acrylic acid‐co‐2‐acrylamide‐2‐methyl propane sulfonic acid) (CTS‐g‐P(AA‐co‐AMPS)) hydrogel is prepared and used to remove methylene blue (MB) and rhodamine B (RB) mixed dyes from aqueous solutions. The effect of adsorption conditions, including the initial concentrations of dye solutions, contact time, initial pH values, ionic strength, and the adsorbent dosage, on the adsorption capacities is investigated. The maximal adsorption capacity for MB and RB is 936.0 and 556.9 mg/g, respectively. The adsorption isotherms of the mixed dyes are discussed using the extended Langmuir (EL) and the extended Freundlich (EF) isotherm equations. It indicates that the adsorption of both dyes is in good agreement with the extended Freundlich isotherm. Meanwhile, the adsorption processes of both dyes are spontaneous. Adsorption kinetics is in accordance with the pseudo‐second‐order kinetic equation. It is concluded that the available adsorption sites are shared by both kinds of the dye molecules. The difference of the maximal adsorption capacities of the two dyes is due to their different affinity to the adsorbent.